2013
DOI: 10.1128/mbio.00431-13
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of FtsE ATPase and FtsX Extracellular Loops 1 and 2 in FtsEX-PcsB Complex Function in Cell Division of Streptococcus pneumoniae D39

Abstract: The FtsEX protein complex has recently been proposed to play a major role in coordinating peptidoglycan (PG) remodeling by hydrolases with the division of bacterial cells. According to this model, cytoplasmic FtsE ATPase interacts with the FtsZ divisome and FtsX integral membrane protein and powers allosteric activation of an extracellular hydrolase interacting with FtsX. In the major human respiratory pathogen Streptococcus pneumoniae (pneumococcus), a large extracellular-loop domain of FtsX (ECL1FtsX) is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
86
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 39 publications
2
86
1
Order By: Relevance
“…The energy required for the coordinated movement of a-helices in the CC PcsB domain is in all likelihood produced by hydrolysis of ATP by FtsE. In agreement with this, it has been shown that the conserved amino acids in the ATP binding site of FtsE are essential for pneumococcal growth, supporting the idea that ATPase activity by FtsE is required for FtsEX-PcsB signalling and coordination of cell separation 14 . Once released, the catalytic domain would not require further opening of the active-site loops.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The energy required for the coordinated movement of a-helices in the CC PcsB domain is in all likelihood produced by hydrolysis of ATP by FtsE. In agreement with this, it has been shown that the conserved amino acids in the ATP binding site of FtsE are essential for pneumococcal growth, supporting the idea that ATPase activity by FtsE is required for FtsEX-PcsB signalling and coordination of cell separation 14 . Once released, the catalytic domain would not require further opening of the active-site loops.…”
Section: Discussionsupporting
confidence: 66%
“…To release the CHAP domain, the 'molecular tweezers', which consists of a1-a3 on one side and a4-a5 on the other, must be opened on both sides. Previous studies involving Ts and suppressor mutants of PcsB and FtsX, respectively, revealed mutations in the large (ECL1) and small (ECL2) extracellular loops of FtsX that indicate that the FtsXPcsB interaction occurs between these loops and the CC domain of PcsB 13,14 . The Ts mutations in CC PcsB are located just in the middle of a1 and a3 helices and at the base of a4 helix ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations